Self-disclosure and marital satisfaction among Filipino couples (2003)
This is a pilot study conducted to determine self-disclosure among Filipino couples and its association with marital satisfaction. About 45 parents from the UP Child Development Center (UP CDC) participated in the study. A four-part questionnaire gathered the needed data. These were analyzed using percentages, frequencies, ordinal positions, and Spearman Rank Order Correlation test. The findings of the study revealed that disclosure was considered as an essential component of marriage which adds to marital satisfaction. However, they did not seem to put too much emphasis on mutuality and reciprocity. In terms of the content of the disclosure, couples preferred selective disclosure, choosing to discuss positive things over the negative ones, or those which may hurt their spouses. The items disclosed fully were in the areas of money, work and family matters/relationships. No item under the area of personality was included. Marital satisfaction is positively associated with both the respondents' and their spouses' levels of disclosure. Among the recommendations cited, a follow-up study may be done, using a larger number of participants as well as non-verbal disclosure in order to see the congruence between verbal and non-verbal disclosures.
Keywords: Communmication in marriage; Self disclosure